Separated and overlapping neural coding of face and body identity. Issue 13 (25th May 2021) - Foster, Celia; Zhao, Mintao; Bolkart, Timo; Black, Michael J.; Bartels, Andreas; Bülthoff, Isabelle
Abstract: Recognising a person's identity often relies on face and body information, and is tolerant to changes in low‐level visual input (e.g., viewpoint changes). Previous studies have suggested that face identity is disentangled from low‐level visual input in the anterior face‐responsive regions. It remains unclear which regions disentangle body identity from variations in viewpoint, and whether face and body identity are encoded separately or combined into a coherent person identity representation. We trained participants to recognise three identities, and then recorded their brain activity using fMRI while they viewed face and body images of these three identities from different viewpoints. Participants' task was to respond to either the stimulus identity or viewpoint. We found consistent decoding of body identity across viewpoint in the fusiform body area, right anterior temporal cortex, middle frontal gyrus and right insula. This finding demonstrates a similar function of fusiform and anterior temporal cortex for bodies as has previously been shown for faces, suggesting these regions may play a general role in extracting high‐level identity information. Moreover, we could decode identity across fMRI activity evoked by faces and bodies in the early visual cortex, right inferior occipital cortex, right parahippocampal cortex and right superior parietal cortex, revealing a distributed network that encodes person identity abstractly. Lastly, identity decoding was consistently better when participants attended to identity, indicating that attention to identity enhances its neural representation. These results offer new insights into how the brain develops an abstract neural coding of person identity, shared by faces and bodies. Abstract : In this study, we investigated the neural coding of face and body identity. We found that body identity could be decoded across viewpoint from fMRI activity in fusiform and anterior temporal cortex, regions that have previously been shown to encode face identity across viewpoint, suggesting that these regions may play a general role in extracting high‐level identity information. Furthermore, we could decode identity across fMRI activity evoked by faces and bodies, revealing a distributed network that encodes person identity in an abstract manner.